iConnect: A Web-Based Digital Platform for Integrated Management of Large-Scale Events - Amni Najlaa Ahmad Bukhari; Aulia Adly; Iman Shafie Haidzir; Shelena Soosay Nathan; Nurdalila Saji (Emerging Advances in Integrated Technology, 2026)
Efficient event management is essential for organizing academic and research exhibitions, ensuring smooth participation and communication. However, the traditional process often involves manual work and delays in communication. The iConnect Event Registration System is developed to provide an easy-to-use platform for students, lecturers and event organizers to register for events, receive real-time updates, and automatically generate participation certificates. This project follows a prototyping methodology with phases including planning, analysis, design, and implementation after prototype validation. The method were chosen due to the approach where a simplified, functional version of a system is built, tested, and refined based on user feedback and widely used in both specialized engineering projects and general software development. Key features of the system include simple and fast registration processes, automatic generation of certificates upon event completion, and instant notifications to keep participants informed of event updates and statuses. The system benefits students and event organizers by reducing manual work, improving communication, and enhancing user experience throughout the event cycle, the success of the project will be evaluated based on user satisfaction, reliability of certificate generation, and effectiveness of notification delivery. In conclusion, the iConnect system aims to offer a practical and scalable solution to support academic event management.